Analysis of The Relationship between E-Service Quality, E-Satisfaction, and E-Loyalty in Indonesia E-Commerce Sector - Yoga Ajie Kristanto (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This study analyzes the relationship between e-service quality, e-satisfaction, and e-loyalty in the e-commerce sector in Indonesia. The sample used in this study had used or bought goods from e-commerce, had an account or membership of one or more e-commerce operating in Indonesia, both men and women with an age range of 17-60 years totaling 200 respondents. This study used the variables e-service quality, e-satisfaction, and e-loyalty. The data collection technique in this study was using a questionnaire which was then analyzed using the Structural Equation Model (AMOS v 23). The results indicate that e-service quality has a significant positive effect on e-satisfaction. E-satisfaction has a significant positive relationship with e-loyalty. E-service quality has a significant positive effect on e-loyalty. E-satisfaction can mediate the relationship between e-service quality and e-loyalty in a significant positive manner.